Barriers of adopting E-Learning in developing countries - Fahad A.; Hassan Z.; Salman Z. (Medwell Journals, 2023)
This research lays out the main research idea in addressing the question as to the purpose of the study and related elements. The initial topics delve into the research idea by introducing it and laying the foundation for research implementation. Besides that, the initial topics also state the problem statement, research objectives, questions, its significance, research framework and its scope. The final sub-topic represents the summary of this research. Medwell Journals, 2016.